Rozwiąż równania
a) (3x - 2)(x + 1) = 3x(do potęgi drugiej) - 5
b) (4 - 5x)(2 + x) = -(4 + 5x(do potęgi drugiej)
c) 4x(do potęgi drugiej) - 2x = (2x +1)(2x - 3)
d) 3x(2x + 5) = (x + 3)(6x +2)
Pliss szybko



Odpowiedź :

Hej!

(3x - 2)(x + 1) = 3x² - 5

3x² + 3x - 2x - 2 = 3x² - 5

3x² + 3x - 2x - 3x² = -5 + 2

x = -3

(4 - 5x)(2 + x) = -(4 + 5x²)

8 + 4x - 10x - 5x² = -4 - 5x²

4x - 10x - 5x² + 5x² = -4 - 8

-6x = -12 / : (-6)

x = 2

4x² - 2x = (2x + 1)(2x - 3)

4x² - 2x = 4x² - 6x + 2x - 3

4x² - 2x - 4x² + 6x - 2x = -3

2x = -3 / : 2

x = -1,5

3x(2x + 5) = (x + 3)(6x + 2)

6x² + 15x = 6x² + 2x + 18x + 6

6x² + 15x - 6x² - 2x - 18x = 6

-5x = 6 / : (-5)

x = -1,2

Pozdrawiam! - Julka